Sustainable Purchasing Trends Among Gen-Z: Understanding Through Online Media - Nata Rosalia; Muhammad Aris Syafi; Hendri Hermawan Adinugraha (PT. Altaf Publishing Corp, 2025)
This study discusses sustainable purchasing trends among Generation Z influenced by online media such as social media, blogs, and marketplaces. Generation-Z has a high awareness of sustainability and chooses ethical and environmentally friendly products. They are exposed to various content that introduces sustainable products through influencers and online communities, which shapes their awareness and consumption choices. This study uses qualitative methods, involving in-depth interviews, participant observation, and documentation to understand the sustainable consumption behavior of Gen-Z in Wonokerto District. The findings show that online media plays a major role in increasing sustainability awareness and influencing product preferences among Gen-Z. This study offers insights for industry players to design effective marketing strategies and for policymakers to promote sustainable consumption.